DESAIN PRODUK VIRTUAL LAB GEOMETRI DI UNIVERSITAS TERBUKA SEMARANG SEBAGAI PARADIGMA PEMBELAJARAN ABAD 21 - Nurmawati Nurmawati; Lusi Rachmiazasi Masduki; Eem Kurniasih (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
The current virtual laboratory conditions are developing so rapidly, one of the indicators is the large number of Mathematics students, both PTN and PTS in Central Java, who are looking for references related to online geometry course practicums between lectures. This raises concern as a lecturer in adding value to lectures, which are adapted to the current 21st century learning era by creating a virtual laboratory based on Virtual Reality geometry courses, research methods using the ADDIE R & D model (Analysis, Design, Develop, Implementation and Evaluation) in this research only up to 3 steps because time constraints in product creation and validation, the results of virtual geometry lab products are expected to be able to display virtual and augmented reality which can increase student motivation and learning outcomes, based on the validation of media experts and material experts on geometry lab virtual products obtaining grades of 91 and 94 a This means that virtual geometry lab products are very suitable for learning geometry during a pandemic at the Open University of Semarang